A mechanism study of acid-assisted oxidative stabilization of asphaltene-derived carbon fibers. (October 2021) - Leistenschneider, Desirée; Zuo, Peiyuan; Kim, Yuna; Abedi, Zahra; Ivey, Douglas G.; de Klerk, Arno; Zhang, Xuehua; Chen, Weixing
Abstract: The development of inexpensive carbon fiber precursors is necessary to meet the future demands of carbon fibers. This work shows how asphaltenes, which are obtained as a by-product in bitumen production, can play an important role as such inexpensive carbon fiber precursors. To synthesize carbon fibers from asphaltene, stabilization by means of oxidizing acids (HNO3 and H2 SO4 ) was developed. Stabilization could not be achieved by a non-oxidizing acid (HCl). The reactions leading to fiber stabilization was investigated for nitric acid treatment, which led to oxidation and the incorporation of nitro-groups. Further thermal treatment caused an increase in C/H ratio that was related to decomposition of nitro-groups, which facilitated air oxidation and other reactions leading to the loss of volatile hydrogen-rich products, such as light hydrocarbons. Additionally, the influence of the acid concentration during treatment on fiber properties, such as fiber diameter, composition, tensile strength and elastic modulus, has been examined. The application of the acid treatment leads to carbon fibers with good tensile properties, with a tensile strength and elastic modulus of 811 MPa and 32.7 GPa, respectively. The overall yield of carbon fibers is 37 – 38 wt.%.